Województwo śląskie według spisu z 9 grudnia 1931 roku - Stańczyk, Elżbieta (Silesian Voivodeship by National Population Census on December 9th 1931, 2006)
In the article one presented the state and the structure of the population of the Silesian province according to the register from the day 9 December 1931. From accessible data it results that the Silesian province was characterized the highest density of population among all provinces and with the greatest degree of the concentration of the population i.e. with the greatest deviation of the Lorenzcurve from the line of the uniform distribution.One obtained also different on Silesia than in remaining provinces the demographic structure of the population according to: the confession, the language, the age, the social position and sources of holding.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 33-54